INNOVATIONS OF THE IMPLEMENTATION OF THE NEW LAW "FOR CIVIL SERVANTS" IN THE REPUBLIC OF ALBANIA, THE FUNCTION OF CONTEMPORARY PUBLIC ADMINISTRATION - Julejda Gerxhi (European Scientific Journal, ESJ, 2015)
Civil servants are those employees who serve the public interest through their performance, and therefore labor relations for this category are regulated by the law of "Civil Servant" and not the general provisions of labor legislation. Given that it is a law that serves the public administration, it aims to regulate labor relations for civil servants so that they can contribute to a better service to the public interest. This is why having a good civil service is considered as a state governance. In this paper, the main purpose is to address innovations of the new Law "On Civil Servants" in Albania, in order to reform public administration. Entry into force of this law has given a chance to Albanian public administration, to handle tasks as a small state, but effective, being renovated through fair competition and creates opportunities for professional and career. This law enables the administration based on decision-making processes transparent, inclusive and responsive to public. Public administration reform within the frame of this law, brought a radical change in terms of the relationship of state employees, at the workplace. Work in public administration can not be considered as a job where only the employee benefits from the advantages and comfort that the post provides without giving in return for which it provides its task. This law puts an end to this model, to restore civilian employee in the civil service through professional progress and efficiency of the service provided. In these conditions, public administration Its main challenge is in order to increase public confidence through increased quality of service, in compliance with European standards.